2011
DOI: 10.1088/1748-9326/6/4/045214
|View full text |Cite
|
Sign up to set email alerts
|

Regional methane emission from West Siberia mire landscapes

Abstract: Methane emissions from mires in all climate-vegetation zones of West Siberia (forest steppe, subtaiga, south taiga, middle taiga, north taiga, forest tundra and tundra) were measured using a static chamber method. The observed fluxes varied considerably from small negative values in forested bogs and palsa to hundreds of mgC m −2 h −1 in ponds and wet hollows. Observed data were consolidated in the form of the empirical model of methane emissions designated as the 'standard model'. The model is based on median… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
101
2
14

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(137 citation statements)
references
References 21 publications
12
101
2
14
Order By: Relevance
“…There is a need for integration of methane flux measurements on the model of the FLUXNET activity (http://fluxnet.ornl.gov/). This would allow further refinement of the model parameterizations (Turetsky et al, 2014;Glagolev et al, 2011). A comparison of the model ensemble estimates against bottom-up inventory for western Siberia by Glagolev et al (2011) made by Bohn et al (2015) showed that there still is a sizable disagreement between their results.…”
Section: Regional Methane Emissions Per Source Categorymentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need for integration of methane flux measurements on the model of the FLUXNET activity (http://fluxnet.ornl.gov/). This would allow further refinement of the model parameterizations (Turetsky et al, 2014;Glagolev et al, 2011). A comparison of the model ensemble estimates against bottom-up inventory for western Siberia by Glagolev et al (2011) made by Bohn et al (2015) showed that there still is a sizable disagreement between their results.…”
Section: Regional Methane Emissions Per Source Categorymentioning
confidence: 99%
“…This would allow further refinement of the model parameterizations (Turetsky et al, 2014;Glagolev et al, 2011). A comparison of the model ensemble estimates against bottom-up inventory for western Siberia by Glagolev et al (2011) made by Bohn et al (2015) showed that there still is a sizable disagreement between their results. A more complete analysis of the literature for freshwater emissions has led to a 50 % increase of the reported range compared to Kirschke et al (2013).…”
Section: Regional Methane Emissions Per Source Categorymentioning
confidence: 99%
“…[8] To begin, we collected direct CH 4 flux chamber measurements of wetland ecosystems in the northern high latitudes from peer-reviewed literature [e.g., Glagolev et al, 2011;Levy et al, 2011]. Our data contain CH 4 flux chamber measurements from 34 sites, covering a range of wetland types under various field conditions (Table 1 and Figure 1).…”
Section: Data Organizationmentioning
confidence: 99%
“…Globally, wetlands are the largest natural source of CH 4 emissions to the atmosphere (IPCC, 2013). Because wetland CH 4 emissions are highly sensitive to soil temperature and moisture conditions (Saarnio et al, 1997;Friborg et al, 2003;Christensen et al, 2003;Moore et al, 2011;Glagolev et al, 2011;Sabrekov et al, 2014), there is concern that they will provide positive feedback to future climate warming (Gedney et al, 2004;Eliseev et al, 2008;Ringeval et al, 2011). This risk is particularly important in the world's high latitudes because they contain nearly half of the world's wetlands (Lehner and Döll, 2004) and because the high latitudes have been and are forecast to continue experiencing more rapid warming than elsewhere (Serreze et al, 2000;IPCC, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Peatlands are a type of wetland containing deep deposits of highly porous, organic-rich soil, formed over thousands of years under waterlogged and anoxic conditions, which inhibit decomposition (Gorham, 1991;Frolking et al, 2011). Within the porous soil, the water table is often only a few centimeters below the surface, leading to anoxic conditions and CH 4 emissions even when no surface water is present (Saarnio et al, 1997;Friborg et al, 2003;Glagolev et al, 2011). This condition can lead to an underestimation of wetland area when using satellite surface water products as inputs to wetland methane emissions models.…”
Section: Introductionmentioning
confidence: 99%